Locking beam influence on behavior of reinforced concrete two pile caps with embedded socket - Barros, Rodrigo; Giongo, José Samuel (Acta Scientiarum. Technology, 2014)
This paper analyzes the behavior of reinforced concrete two pile caps with embedded socket, used as connection in precast concrete structures. To this end, it was specifically studied the effect of the locking beam on the pile caps when supported by the lateral walls of the socket. A three-dimensional numerical analysis was developed using a software based on the finite element method (FEM), which considered the nonlinear physical behavior of the materials. It was found that for strut angle inclination close to 45Âº, the pile caps showed the same behavior, independent of the wall interfaces. The results indicated that the presence of a locking beam has no significant influence on the pile caps behavior and that the socket wall is able to effectively transfer the force from the beam to the piles. Â